Study of Thermal Comfort In Cafes In Bandung - Grace Gunawan; Hartanto Budiyuwono; Yasmin Suriansyah (Eduvest - Journal of Universal Studies, 2022)
The purpose of this study was to determine the study of thermal comfort in cafes in Bandung. Indonesia is a country with a tropical climate because its geographical position is on the equator. According to data from the Meteorology, Climatology and Geophysics Agency, the average humidity and temperature in 2020 is 27.30C. The method used to analyze the object of this study is a quantitative method with the formula of Thermal Equilibrium, quantitative research is defined as research based on empirical experience that collects data in the form of numbers that can be calculated and in numerical form. This research was conducted with a quantitative approach by performing calculations using the heat balance method to determine the heat in the 3 study objects and what factors most influence the cooling load in the 3 study objects. Human comfort at Noah's Barn Coffeenery, Amber Field Coffee cannot be separated from the thermal comfort factor. Based on the calculation of the thermal balance in the three cafes, more than 50% of the heat in the room comes from interior heat sources, especially electronic equipment and lighting and humans are the biggest heat contributor in the cafe dining area. Each cafe has a different heat source, therefore, each room has a different solution. The heat in Naoh's Barn Coffeenery is 25.2412504 kW